2009 International Conference on Computational Intelligence and Software Engineering 2009
DOI: 10.1109/cise.2009.5363890
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Social Network to Improve Recommender System for Group Learning Support

Abstract: We refer to a new generation of web technologies such as social networking to address a recommender system that emphasize online collaborative learning. We propose an approach for improving recommender system through exploiting the learners note taking activity. We maintain that notes' features can be exploited by collaborative learning systems in order to enrich and extend the user profile and improve personalized learning. Thus our approach stresses collaborative note as a new and powerful kind of feedback a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
(17 reference statements)
0
5
0
2
Order By: Relevance
“…Song et al, 2011;I. Song et al, 2011;Sun et al, 2015;Szabó et al, 2012;Szymański & Rzeniewicz, 2016;Takács et al, 2008;Takáes et al, 2009;Tsapatsoulis et al, 2015;Tsuji et al, 2014;Verma et al, 2016;Vialardi et al, 2011;Wan et al, 2009;Wang et al, 2012;Wei et al, 2011;Xin et al, 2014;Yan et al, 2013;Yap et al, 2005 Unsupervised learning 46 24 (Bar et al, 2013;Bjelica, 2010;Bouneffouf et al, 2012;Buettner, 2016;Degemmis et al, 2007;Devi & Venkatesh, 2013;Elmongui et al, 2015;Z. Fan et al, 2016;Ghazarian & Nematbakhsh, 2015;Halder et al, 2014;Hassan et al, 2010; T.-J.…”
Section: Big Data Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Song et al, 2011;I. Song et al, 2011;Sun et al, 2015;Szabó et al, 2012;Szymański & Rzeniewicz, 2016;Takács et al, 2008;Takáes et al, 2009;Tsapatsoulis et al, 2015;Tsuji et al, 2014;Verma et al, 2016;Vialardi et al, 2011;Wan et al, 2009;Wang et al, 2012;Wei et al, 2011;Xin et al, 2014;Yan et al, 2013;Yap et al, 2005 Unsupervised learning 46 24 (Bar et al, 2013;Bjelica, 2010;Bouneffouf et al, 2012;Buettner, 2016;Degemmis et al, 2007;Devi & Venkatesh, 2013;Elmongui et al, 2015;Z. Fan et al, 2016;Ghazarian & Nematbakhsh, 2015;Halder et al, 2014;Hassan et al, 2010; T.-J.…”
Section: Big Data Technologiesmentioning
confidence: 99%
“…Zhang et al, 2009) Social 14 (Aouay et al, 2014;Cai et al, 2010Cai et al, , 2012Diaby et al, 2013;Elmongui et al, 2015;Hassan et al, 2010;Islam et al, 2015;Krzywicki et al, 2015;Y. Song et al, 2011;Verma et al, 2016;Wan et al, 2009;Yan et al, 2013;Yuan et al, 2014;K. Zhao & Pan, 2015) Academic 12 (Das et al, 2013;Hernández del Olmo et al, 2009;Huang & Nikulin, 2014;Krohn-Grimberghe et al, 2011;Luong, Huynh, Gauch, Do, & Hoang, 2012;Middleton et al, 2004;Montañés et al, 2009;Oyama et al, 2012;Pecli et al, 2015;Vialardi et al, 2011;Xin et al, 2014) News 11 (Bellogín et al, 2011;Brouard & Pomot, 2016;Buabin, 2012;Das et al, 2013;Z.…”
Section: Performance Metricsunclassified
See 1 more Smart Citation
“…Social science research has revealed that people build social relationships with each other, and these relationships may help them locate either information or services more effectively. Wan et al (26) found that a collaborative group-learning environment in which students could express their thoughts, voice their opinions, and share their experiences had a positive outcome.…”
Section: Group Collaborationmentioning
confidence: 99%
“…In addition, new technology and web-based education has changed old learning paradigms into a new opportunity to learn "anywhere and anytime". During their study Wan et al (26) established a new student user profile. This profile included abilities, knowledge, and learning preferences.…”
Section: Group Collaborationmentioning
confidence: 99%